Demonic History From Goethe to the Present - Wetters, Kirk (Northwestern University Press, 2015)
In this ambitious book, Kirk Wetters traces the genealogy of the demonic in German literature from its imbrications in Goethe to its varying legacies in the work of essential authors, both canonical and less well known, such as Gundolf, Spengler, Benjamin, Lukács, and Doderer. Wetters focuses especially on the philological and metaphorological resonances of the demonic from its core formations through its appropriations in the tumultuous twentieth century.Propelled by equal parts theoretical and historical acumen, Wetters explores the ways in which the question of the demonic has been employed to multiple theoretical, literary, and historico-political ends. He thereby produces an intellectual history that will be consequential both to scholars of German literature and to comparatists.